Pharmacokinetics of Sucralose and Acesulfame-Potassium in Breast Milk Following Ingestion of Diet Soda. Issue 3 (March 2018) - Rother, Kristina I.; Sylvetsky, Allison C.; Walter, Peter J.; Garraffo, H. Martin; Fields, David A.
ABSTRACT: Objective: The aim of this study was to determine sucralose and acesulfame-potassium (ace-K) pharmacokinetics in breast milk following maternal ingestion of a diet soda. Methods: Thirty-four exclusively breast-feeding women (14 normal-weight, 20 obese) consumed 12 ounces of Diet Rite Cola, sweetened with 68-mg sucralose and 41-mg ace-K, before a standardized breakfast meal. Habitual non-nutritional sweeteners intake was assessed via a diet questionnaire. Breast milk was collected from the same breast before beverage ingestion and hourly for 6 hours. Results: Owing to one mother having extremely high concentrations, peak sucralose and acesulfame-potassium concentrations following ingestion of diet soda ranged from 4.0 to 7387.9 ng/mL (median peak 8.1 ng/mL) and 299.0 to 4764.2 ng/mL (median peak 945.3 ng/mL), respectively. Conclusions: Ace-K and sucralose transfer into breast milk following ingestion of a diet soda. Future research should measure concentrations after repeated exposure and determine whether chronic ingestion of sucralose and acesulfame-potassium via the breast milk has clinically relevant health consequences.